Efficiency Analysis of Sharia Go Public Companies in The Consumer Services Sector During The Covid-19 - Anggita Nurcahyani,; Syarifudin , Efi; Nurhab, Muhamad Irpan (Jurnal Iqtisaduna, 2024)
This research aims to analyze the efficiency level in the sharia-go public industry in the consumer service sector during the Covid-19 pandemic. This research uses a quantitative data envelopment analysis (DEA) approach. Secondary data is obtained through financial reports, which will then be measured by several variables in this research, namely total assets, operational expenses, Inventory, business income, and total asset turnover (TATO) with Maxdea Basic 8 software. The DEA model used is Variable Return to Scale (VRS). The results showed that the companies that efficiently obtained a score of 100% during 2020–2022 were PT Pembangunan Jaya Ancol (PJAA) and PT Fast Food Indonesia (FAST). Both companies operating in the tourism and restaurant sectors were able to maintain optimal performance during Covid-19. Strengthening Muslim-friendly services can be used as a strategy to restore the tourism, hotel, and restaurant business sector after the COVID-19 pandemic.